2022
DOI: 10.1007/s00018-022-04219-z
|View full text |Cite
|
Sign up to set email alerts
|

Type I interferon-mediated tumor immunity and its role in immunotherapy

Abstract: Immune checkpoint blockade (ICB) therapies have achieved remarkable clinical responses in patients with many different types of cancer; however, most patients who receive ICB monotherapy fail to achieve long-term responses, and some tumors become immunotherapy-resistant and even hyperprogressive. Type I interferons (IFNs) have been demonstrated to inhibit tumor growth directly and indirectly by acting upon tumor and immune cells, respectively. Furthermore, accumulating evidence indicates that endo- and exogeno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
76
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(99 citation statements)
references
References 171 publications
1
76
0
Order By: Relevance
“…Mechanistically, tumour-derived HMGB1 induces the production of type I IFNs in dendritic cells via the TLR4-MyD88 pathway, and tumour-derived DNA activates the cGAS/STING pathway to drive the expression of type I IFNs through chaperoning HMGB1, autophagosome, exosome, LL37 or CLEC9A into dendritic cells. 44 Studies also pointed out that IFNα promotes protein ISGylation in a SUMO3dependent manner through TRIM25, and enhanced IFNα-induced holo-ISGylation can also directly protect some proteins from proteasomal degradation. 45 Secondly, miR-2909, known to play a role in immunity and cancer, has been shown to upregulate ISGylation system through STAT1.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistically, tumour-derived HMGB1 induces the production of type I IFNs in dendritic cells via the TLR4-MyD88 pathway, and tumour-derived DNA activates the cGAS/STING pathway to drive the expression of type I IFNs through chaperoning HMGB1, autophagosome, exosome, LL37 or CLEC9A into dendritic cells. 44 Studies also pointed out that IFNα promotes protein ISGylation in a SUMO3dependent manner through TRIM25, and enhanced IFNα-induced holo-ISGylation can also directly protect some proteins from proteasomal degradation. 45 Secondly, miR-2909, known to play a role in immunity and cancer, has been shown to upregulate ISGylation system through STAT1.…”
Section: Discussionmentioning
confidence: 99%
“…Type I interferons (IFN-I) are pleotropic cytokines that function in antimicrobial immunity, tumor immunity, and metabolic regulation. However, persistent and unrestrained IFN-I signaling is linked to autoimmune diseases, type I interferonopathies, and organ system failure (Crow and Stetson, 2021; Lei et al, 2021; McNab et al, 2015; Wu et al, 2016; Yu et al, 2022). We recently reported that mtDNA instability and chronic activation of cGAS-STING-IFN-I signaling potentiate age-related tissue pathology in the polymerase gamma (POLG) mutator model of mtDNA disease (Lei et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…IFN was discovered by Issacs and Lindenmann in 1957 during their study on phenomenon of virus interference[43], which are classified by type 1, type 2 and type 3. Type 1 IFN is secreted by cells infected with virus and has strong antiviral, antitumor, immunomodulatory properties; Type 2 IFN, secreted by activated T cells, is mainly involved in the immune regulation; Most cells could secrete type 3 IFN, which generate beneficial mucosal immunomodulatory effects[44-46]. Among them, type 1 and type 3 IFN are classical antiviral interferons.…”
Section: Introductionmentioning
confidence: 99%